Fantastic beasts and where to find them [videorecording (Blu-Ray + DVD)] - Rowling, J. K.; Redmayne, Eddie, 1982-; Waterston, Katherine; Fogler, Dan; Sudol, Alison, 1984-; Miller, Ezra; Morton, Samantha; Voight, Jon, 1938-; Ejogo, Carmen, 1974-; Farrell, Colin, 1976-; Howard, James Newton; Atwood, Colleen; et al. (Warner Bros. Entertainment Inc., 2017)
It opens in 1926 as Newt Scamander has just completed a global excursion to find and document an extraordinary array of magical creatures. Arriving in New York for a brief stopover, he might have come and gone without incident, were it not for a No-Maj (American for Muggle) named Jacob, a misplaced magical case, and the escape of some of Newt's fantastic beasts, which could spell trouble for both the wizarding and No-Maj worlds.